Opportunistic intestinal parasites and CD4 count in HIV infected people (Journal of Pathology of Nepal, 2011)
Background: Opportunistic intestinal infections cause a significant morbidity and mortality among the HIV infected people. The present study was undertaken to find the prevalence of intestinal opportunistic parasitic infections among the HIV infected populace in eastern Nepal and to correlate the occurrence with the CD4 T cell counts. Materials and Methods: Stool from 122 HIV infected people were examined microscopically for the presence of parasitic ova/cyst. CD4 T cell enumeration was done using FACS Count (Becton Dickinson). Stool from 100 age matched HIV negative controls were also examined. Results: A male preponderance in the parasite positivity was seen. Twenty five of symptomatic and 2.8% of asymptomatic harboured one or more intestinal parasites.12.3% of the study population had intestinal parasitoses with 7.3% being infected with opportunistic parasites. The mean CD4 count of the subjects was 307 while those with parasitoses were 204. A statistically significant difference was seen between the CD4 counts of symptomatic and asymptomatic patients. Conclusion: Coccidian parasites are frequent opportunistic intestinal parasites infecting HIV infected patients. A lowered CD4 count predisposes to acquisition of these agents. Regular monitoring of CD4 counts and screening for these opportunistic agents in the HIV infected will help reduce the mortality and morbidity associated with infections by these agents. Keywords: HIV; Opportunistic infection; CD4 count; AIDS DOI: http://dx.doi.org/10.3126/jpn.v1i2.5405 JPN 2011; 1(2): 118-121